Hippocampal Astrocytes in Migrating and Wintering Semipalmated Sandpiper Calidris pusilla - Carvalho-Paulo, Dario; de Morais Magalhães, Nara G.; de Almeida Miranda, Diego; Diniz, Daniel G.; Henrique, Ediely P.; Moraes, Isis A. M.; Pereira, Patrick D. C.; de Melo, Mauro A. D.; de Lima, Camila M.; de Oliveira, Marcus A.; Guerreiro-Diniz, Cristovam; Sherry, David F.; et al. (Frontiers in Neuroanatomy, 2018)
Seasonal migratory birds return to the same breeding and wintering grounds year after year, and migratory long-distance shorebirds are good examples of this. These tasks require learning and long-term spatial memory abilities that are integrated into a navigational system for repeatedly locating breeding, wintering, and stopover sites. Previous investigations focused on the neurobiological basis of hippocampal plasticity and numerical estimates of hippocampal neurogenesis in birds but only a few studies investigated potential contributions of glial cells to hippocampal-dependent tasks related to migration. Here we hypothesized that the astrocytes of migrating and wintering birds may exhibit significant morphological and numerical differences connected to the long-distance flight. We used as a model the semipalmated sandpiper Calidris pusilla, that migrates from northern Canada and Alaska to South America. Before the transatlantic non-stop long-distance component of their flight, the birds make a stopover at the Bay of Fundy in Canada. To test our hypothesis, we estimated total numbers and compared the 3-D morphological features of adult C. pusilla astrocytes captured in the Bay of Fundy, (n = 249 cells) with those from birds captured in the coastal region of Bragança, Brazil, during the wintering period (n = 250 cells). Optical fractionator was used to estimate the number of astrocytes and for 3D reconstructions we used hierarchical cluster analysis. Both morphological phenotypes showed reduced morphological complexity after the long-distance non-stop flight, but the reduction in complexity was much greater in Type I than in Type II astrocytes. Coherently, we also found a significant reduction in the total number of astrocytes after the transatlantic flight. Taken together these findings suggest that the long-distance non-stop flight altered significantly the astrocytes population and that morphologically distinct astrocytes may play different physiological roles during migration.